2021
DOI: 10.1136/openhrt-2021-001785
|View full text |Cite
|
Sign up to set email alerts
|

Combined anticoagulant and antiplatelet therapy is associated with an improved outcome in hospitalised patients with COVID-19: a propensity matched cohort study

Abstract: BackgroundCOVID-19 is a respiratory disease that results in a prothrombotic state manifesting as thrombotic, microthrombotic and thromboembolic events. As a result, several antithrombotic modalities have been implicated in the treatment of this disease. This study aimed to identify if therapeutic anticoagulation (TAC) or concurrent use of antiplatelet and anticoagulants was associated with an improved outcome in this patient population.MethodsA retrospective observational cohort study of adult patients admitte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Among the 8318 articles initially retrieved through our literature search, 21 fulfilled the inclusion criteria and were included in our analysis [ 11 , 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 8318 articles initially retrieved through our literature search, 21 fulfilled the inclusion criteria and were included in our analysis [ 11 , 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 . A total of 7 studies reported data for intermediate versus prophylactic dose [ 11 , 27 , 28 , 29 , 30 , 34 , 35 ], while 17 studies reported data for therapeutic versus prophylactic dose of thromboprophylaxis [ 12 , 23 , 24 , 25 , 26 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Three studies contributed data for both intermediate versus prophylactic and therapeutic versus prophylactic dose analyses [ 29 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 has symptoms similar to those of contracting a mild flu (fever, cough, and malaise), although asymptomatic cases and other atypical symptoms have been reported as well [3,4]. In severe cases, symptoms can rapidly develop and lead to respiratory failure and even multi-organ failure, necessitating admission to the intensive care unit (ICU) and initiating mechanical ventilation [5,6]. In 2020, the number of deaths reported to WHO as a result of COVID-19 was estimated to have exceeded 3.3 million deaths.…”
Section: Introductionmentioning
confidence: 99%